Effects of Time Frame on the Recall Reliability of CFS Symptoms. (September 2015) - Evans, Meredyth; Jason, Leonard A.
This study serves as an investigation of the reliability of symptom data as reported by individuals with chronic fatigue syndrome (CFS), across three recall time frames (the past week, the past month, and the past 6 months), and at two assessment points (with 1 week in between each assessment). Multilevel model analyses were used to determine the optimal recall time frame, in terms of test -retest reliability, for each of the Fukuda et al. (1994) case defining symptoms. Results suggested that the optimal time frame for reliably reporting CFS symptoms was six months for sore throat, lymph node pain, muscle pain, post-exertional malaise, headaches, memory/concentration difficulties, and unrefreshing sleep. For joint pain, the optimal time frame was one month. Researchers who are interested in the assessment of CFS symptoms need to take recall time frame into account, especially when the intended goal is to standardize and improve the methods used to reliably and accurately diagnose this complex illness.